Management and cost analysis of cancer patients treated with G-CSF: a cohort study based on the French national healthcare insurance database. (2nd December 2017) - Tilleul, Patrick; Jacot, William; Emery, Corinne; Lafuma, Antoine; Gourmelen, Julie
Abstract: Objectives: To describe the management and costs associated with G-CSF therapy in cancer patients in France. Methods: This study analyzed a representative random population sample from the French national healthcare insurance database, focusing on 1, 612 patients with hematological or solid malignancies who were reimbursed in 2013 or 2014 for at least one G-CSF treatment dispensed in a retail pharmacy. Patient characteristics and treatment costs were analyzed according to the type of cancer. Then the costs and characteristics of patients associated with the use of different G-CSF products were analyzed in the sub-set of breast cancer patients. Results: The most frequent malignancies in the database population were breast cancer (23.3%), hematological malignancies (22.2%), and lung cancer (12.4%). The reimbursed G-CSF was pegfilgrastim in 34.1% of cases, lenograstim in 26.7%, and filgrastim in 17.9%. More than one G-CSF product was reimbursed to 21.3% of patients. The total annual reimbursed health expenses per patient, according to the type of G-CSF, were €27, 001, €24, 511, and €20, 802 for patients treated with filgrastim, lenograstim, and pegfilgrastim, respectively. Ambulatory care accounted for, respectively, 35%, 38%, and 41% of those costs. In patients with breast cancer, ambulatory care cost was €7, 915 with filgrastim, €7, 750 with lenograstim, and €6, 989 with pegfilgrastim, and the respective cost of G-CSF was €1, 733, €1, 559, and €3, 668. Conclusion: All available G-CSF products have been shown to be effective in cancer patients, and both daily G-CSFs and pegylated G-CSF are recommended in international guidelines. Nevertheless, this analysis of G-CSF reimbursement indicates that the choice of product can markedly affect the total cost of ambulatory care.